Cristi Steyaert: capstone - Steyaert, Cristi, artist (Colorado State University. Libraries, 2017)
The artist's statement: In our contemporary society, the subject of addiction has been a suppressed topic of discussion. The awareness of the impact of addiction that affects an individual and those who are in that individual's life is never spoken about. Advertisements or campaigns focus on communicating the message of "Do not use because drugs are bad" which overall is not an effective way to show the damage of addiction. My work focuses on the impact of addiction and how it creates damage and destruction. I explore this through the medium of acrylic and working on different surfaces such as masonite board and glass to see how I can visually communicate the dangerous aspect of using an illicit substance. I also explore how the representation of this subject is communicated through natural rendering of the human body or aspects of the human body in a graffiti styling. The focus of these works is to show the audience and make them comprehend what it is like to be in the position of the addictive individual. I want the audience to explore the subject matter by bringing awareness to a subject that as a society we tend to ignore if it does not concern us. An example of this is the usage of broken glass to show the destructive element of what addiction can create. This work reflects the artist's personal experience with family members and significant others who have used a substance or multiple substances. In addition, I bring the experience I have gained while working the field of addiction counseling with at risk youth as a source of inspiration for these works. The impact of addiction is a real dilemma that is growing in our society and it is overlooked. As an artist who is inspired by those who are personally currently dealing with or in the past have dealt with this in their life, I feel it is my job to create these works. I want to show the impact of addiction and bring awareness to others but to also show that there is a human element to this subject. There is more to an artwork than just the subject matter of an individual being rendered, there is a story and a cause for why it is being created. I want my audience to explore this and explore the person behind the substance.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting